Breast thermography, 1200 observations - Pressa, Carlos; Laviña, Raúl; Glossa, Walter; Albo, Manuel; del Campo, Alberto; Mate, Miguel (Cirugía del Uruguay, 1984)
The experience of a multidisciplinary group for the study of breast pathology, with special reference to one diagnostic method: plate thermography is presen• ted. Special considerations are done referred to diag• nostic methodology, results obtained as well to prognosis and follow up.